Exploring the social determinants of health from the perspectives of people with spinal cord injuries: A disability studies approach - Alfiya Battalova; Sheemouna Gurung; Hailey-Thomas Ford; Gurkaran Singh; W. Ben Mortenson; Habib Chaudhury (Elsevier, 2024)
The social determinants of health is an internationally recognized approach to analyzing the impact of non-medical factors on individual health. However, disability is mostly associated with inherent vulnerability without recognition of the social factors. The goal of this qualitative study is to examine the lived experiences of persons living with spinal cord injury (SCI) in coping and managing their health and functioning and to explore an interaction between their embodied experiences and structural issues that contribute to health and wellbeing of people with spinal cord injuries. A thematic analysis of 30 semi-structured interviews generated three themes that highlighted the tensions between the materiality of disability and the barriers associated with stigma, between the self-management strategies and the healthcare access, and finally between access to the formal supports and the invisible costs of living with a spinal cord injury. The findings emphasize the need to re-evaluate public health approaches, recognize the linkages between inequalities linked to disability, and incorporate an embodiment lens from a disability justice perspective.